Interoperable e-Government in Malaysia: A framework for transparent public delivery system / Hayati Harudin - Hayati , Harudin (2007)
We are now living in an information age. ICT will never become a cliché. E-government is what reinvents the public delivery system. This research looks at interoperable e-government in Malaysia and its framework for transparency in public delivery system. The significance of this research profoundly paves the way to support the ICT strategies in public sector to deliver interoperable e-government that enhances public service into excellent service and better governance. This research presents literature review of many areas pertaining to the revolution in public sector, the reinvention of public delivery system with e-government, case studies on e-government adoption and technology trends that are undoubtedly, key to innovate public delivery system. Progressing the e-government maturity model is consistent with how Malaysia has to deal with the public demand. Transparency has emerged as an important agenda even though it may appear to have long been oblivion. Key factors that are determinant to bring transparency in public delivery system are identified. These factors are referred to as interoperable e-government factors. A descriptive framework for these factors was formulated. Data collection through stratified random samples was conducted. Data analysis was performed and the research was able to assess and confirm the hypothesis related to these factors. Empirically, the research is able to conclude that the degree of convenient service delivery and the level of intensely streamlined services are the most significant interoperable e-government factors that bring impact to transparency in public delivery system. Service-Oriented Architecture (SOA) development framework was chosen as the software development framework. SOA is fast moving into mainstreaming applications as it is based on services-oriented approaches that support the service-enablement strategy in implementing interoperable e-government and progressing the maturity model. SOA as a development methodology is also suitable in addressing the complex enterprise architecture that exists in public sector. A system called e-Tourism was developed based on this framework to illustrate the interoperable e-government. E-Tourism is chosen as it implements a real-world application which involves the different facets of public sector interactions; the public delivery channel to deal with citizen, businesses and public at large in promoting this country globally and fostering the domestic economy and the electronic channel that supports a cohesive information exchanges in a collaborative and interoperable environment for cross-functional and cross-agencies services.